K-Means Clustering Gross Participation Rate Regency/City Area In North Sumatra - Sujarwo Sujarwo (Jurnal Mantik, 2022)
The percentage of school-age population in North Sumatra Province is 35.95%. Meanwhile, the average gross participation rate for districts/cities in North Sumatra is for the SD level of 110.71; the average for junior high school level is 93.73; for high school level 89.93; and for College 20.23. In this study, the data was grouped using the K-Means Clustering algorithm on the Regency/City Gross Participation Rate data. The application of the K-Means Clustering algorithm is carried out for up to 5 iterations with 4 clusters. The first cluster includes the areas of Mandailing Natal, Tapanuli Tengah, Asahan with an average Gross Participation Rate  value, the smallest Gross Participation Rate, the largest Gross Participation Rate  respectively 76.39; 73.40; and 81.14. For the Second Cluster covering the Medan City area, the average Gross Participation Rate  value, the smallest Gross Participation Rate , and the largest Gross Participation Rate  are the same, namely 87.50. The Third Cluster covers the areas of Nias, Tapanuli Selatan, Tapanuli Utara, Simalungun, Karo, Deli Serdang, Nias Selatan, Serdang Bedagai, Batu Bara, Nias Utara, Sibolga, Tanjung Balai, Pematang Siantar, Tebing Tinggi, Binjai, Padang Sidempuan, Gunungsitoli with average Gross Participation Rate value, smallest Gross Participation Rate, largest Gross Participation Rate respectively 78.02; 73.45; 85.62. The Fourth Cluster includes Toba, Labuhanbatu, Dairi, Langkat, Humbang Hasundutan, Pakpak Bharat, Samosir, Padang Lawas Utara, Padang Lawas, Labuhan Batu Utara, Nias Barat areas with the average Gross Participation Rate  value, the smallest Gross Participation Rate , the largest Gross Participation Rate  respectively 79,38; 76.84; 81.43.